The efficacy of bimatoprost ophthalmic solution combined with NB-UVB phototherapy in non-segmental and segmental vitiligo: a single-blind randomized controlled study - Silpa-archa, Narumol; Likittanasombat, Surachanee; Apinuntham, Chalermkwan; Pruksaeakanan, Chutipon; Charoenpipatsin, Norramon; Chaiyabutr, Chayada; Wongpraparut, Chanisada (Scientific reports, 2023)
Bimatoprost ophthalmic solution 0.03% (PGF2α analogues) combined with narrowband ultraviolet B (NB-UVB) was reported to be an effective treatment for vitiligo. To investigate the efficacy and safety of treatment for non-segmental/segmental vitiligo compared among bimatoprost ophthalmic solution 0.01% combined with NB-UVB phototherapy, bimatoprost monotherapy, and placebo. This single-blind randomized controlled study enrolled stable Thai vitiligo patients with at least three similarly sized lesions in the same anatomical area. The treatment duration was 6 months with 1- and 2-month post-treatment follow-ups. The 3 selected lesions on each patient were randomized to receive combination therapy, monotherapy, or placebo. The Vitiligo Area Scoring Index (VASI) was used to evaluate lesion response. Of the 25 initially enrolled subjects, 19 patients were analyzed. There were 13 and 6 non-segmental and segmental vitiligo cases, respectively. Eight and 11 cases had face/neck and non-face/neck lesions, respectively. Non-segmental vitiligo and non-face/neck vitiligo patients in the combination group had significant improvement in VASI score at 3 months, 6 months, and at the 2-month follow-up. No side effects were observed/reported. Bimatoprost combination therapy was shown to be safe and effective for treating Thai patients with non-segmental vitiligo in non-face/neck areas of the body.